State of the art: approved and emerging JAK inhibitors for rheumatoid arthritis. (22nd January 2021) - El Jammal, Thomas; Sève, Pascal; Gerfaud-Valentin, Mathieu; Jamilloux, Yvan
ABSTRACT: Introduction: Rheumatoid arthritis (RA) is the most common autoimmune inflammatory arthritis in adults. In the past decade, many treatments have emerged to expand the therapeutic armamentarium of rheumatologists. Among emerging treatments, Janus Kinase inhibitors (JAKi) are promising in treating RA and several other inflammatory conditions, such as psoriatic arthritis (PsA). The JAK/STAT signaling pathway is located downstream certain cytokines receptors that are known to be involved in RA pathogenesis. So far, three JAKi are approved for the treatment of RA, while other JAKi, are under investigation. Areas covered: Herein, the authors review those JAKi approved and emerging for the treatment of RA and provide their expert perspectives on the subject area. Expert opinion: JAKi represent an interesting alternative to other DMARDs when MTX has failed. Long-term extension studies are still ongoing, but one can assume that most of the major safety concerns have already come out. Switching from one JAKi to another DMARD has been little studied, but in such cases, preferring a treatment which does not interfere with the JAK/STAT pathway seems to be a reasonable choice.